Episteme: a podcast model for communicating scientific and research results - Melgarejo-Moreno, Irene; Rodríguez-Rosell, María M. (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The aim of this proposal is to present the essential keys for the launch of 'Episteme', a scientific podcast of the UCAM's 'Communication and Minors' Research Group, which is capable of making research in the area of communication knowledge visible. Through the use of radio language, science could be added to the everyday life of podcasting. This type of agile, simple and short-lived product would make it possible to achieve, without losing scientific rigour, a utopia: open science in the 21st century.